A Study Compares The Effectiveness of Hydrochloric and Sulfuric Acids in Hydrolyzing Jackfruit Seeds into Bioethanol - Elfrida Ginting; Lisnawaty Simatupang; Jhony H. Sembiring (Universitas Tadulako, 2025)
North Sumatera Province, known for its jackfruit production, presents an opportunity to explore jackfruit seeds as a viable bioethanol feedstock. The province’s diverse agricultural commodities generate substantial agricultural waste, currently primarily used as fertilizer. This research aims to diversify waste utilization by focusing on jackfruit, a prominent commodity in North Sumatera, and its potential as a bioethanol feedstock. Given the scarcity of fossil fuels, exploring renewable energy sources, such as bioethanol derived from agricultural waste, is crucial. Identifying accessible sources within regions is vital. Converting jackfruit seed starch into bioethanol requires hydrolysis. This paper compares hydrochloric and sulfuric acid for bioethanol production. Qualitative testing confirmed the presence of bioethanol from both acids. The density of bioethanol produced using hydrochloric acid was 0.825 g/mL, 3.4% higher than the Indonesian standard value. Similarly, the density of bioethanol produced using sulfuric acid was 0.894 g/mL, 12% higher than the standard value. The viscosity of bioethanol produced using hydrochloric acid was 1.02 cp, 12% lower than the standard value. In contrast, bioethanol produced using sulfuric acid had a viscosity of 1.04 cp, 11% lower than the standard value. FTIR spectra of bioethanol treated with hydrochloric acid showed five prominent peaks: 3339.88 cm-1 (OH), 2953.35 cm-1 (-CH), 1643.79 cm-1 (-C-C), 1450.75 cm-1 (-CH3), and 1014.17 cm-1 (-CO). FTIR spectra of bioethanol treated with sulfuric acid showed only two major peaks at 3339.46 cm-1 and 1635.42 cm-1, both corresponding to -OH and -CH. The NMR spectra show three distinct peaks. In ethanol’s proton NMR spectrum, the first doublet at 1.71 and 1.61 ppm is the methyl group protons. The second peak at 2.02 ppm is the hydroxyl group proton. The third doublet at 3.59–3.62 ppm is the methylene group protons. All methods indicate that hydrochloric acid is a more effective hydrolytic agent than sulfuric acid.